Tokenization of Assets: Security Tokens in Liechtenstein and Switzerland - Angelika K. Layr (Milan Law Review, 2021)
Technological innovations invariably lead to legal questions being raised; the sphere of digitalization of physical documents and securities by use of blockchain and other distributed ledger technologies does not constitute an exception. While solutions for many questions can be found within the existing legal framework, some developments call for legislative measures. This paper examines the hurdles in connection with the issuance and transfer of securities by virtue of a mere digital transaction and the approaches of the Liechtenstein and Swiss legislator to overcome them. Both have recognized that entries in distributed ledgers may fulfill the same main functions as the possession of a physical document. While the focus of the selective legal adaptations in Switzerland is on the use of DLT and securities law, the Liechtenstein legislator strives towards a holistic legal and regulatory framework for the entire token economy by introduction of a new set of rules.